2007
DOI: 10.1016/j.bbamem.2007.06.030
|View full text |Cite
|
Sign up to set email alerts
|

Critical amino acid residues of maurocalcine involved in pharmacology, lipid interaction and cell penetration

Abstract: Maurocalcine (MCa) is a 33-amino acid residue peptide that was initially identified in the Tunisian scorpion Scorpio maurus palmatus. This peptide triggers interest for three main reasons. First, it helps unravelling the mechanistic basis of Ca(2+) mobilization from the sarcoplasmic reticulum because of its sequence homology with a calcium channel domain involved in excitation-contraction coupling. Second, it shows potent pharmacological properties because of its ability to activate the ryanodine receptor. Fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
62
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(69 citation statements)
references
References 28 publications
7
62
0
Order By: Relevance
“…This may represent an inhibitory region because of the presence of Glu 12 and Asp 15 , two negatively charged residues. The finding that mutation of Glu 12 to Ala enhances cell penetration of both MCa F (18) and MCa UF (11) further supports this conclusion. MCa UF25-33 -C turned out to have CPP properties also, even though this sequence did not confer a competitive advantage to other MCa CPP analogues as shown in Fig.…”
Section: Nonfolded Truncated Maurocalcine Peptides Are Efficient Cpps-supporting
confidence: 64%
See 2 more Smart Citations
“…This may represent an inhibitory region because of the presence of Glu 12 and Asp 15 , two negatively charged residues. The finding that mutation of Glu 12 to Ala enhances cell penetration of both MCa F (18) and MCa UF (11) further supports this conclusion. MCa UF25-33 -C turned out to have CPP properties also, even though this sequence did not confer a competitive advantage to other MCa CPP analogues as shown in Fig.…”
Section: Nonfolded Truncated Maurocalcine Peptides Are Efficient Cpps-supporting
confidence: 64%
“…First, all of the charged peptides (8 tested) demonstrated CPP properties. These peptides all had the K 22 R 23 R 24 sequence in common, a cluster of basic amino acid residues shown to contribute to the dose efficacy of cell penetration of MCa F in an earlier study (18). Interestingly, removing the last 8 C-terminal amino acids of MCa had little impact on the cell penetration properties (if one compares MCa UF14 -25 -C with MCa UF14 -33 -C).…”
Section: Nonfolded Truncated Maurocalcine Peptides Are Efficient Cpps-mentioning
confidence: 98%
See 1 more Smart Citation
“…LITX also does not form pores in the membrane, as shown by the absence of current when applied to a membrane without RyRs. It was previously noted that the calcines have a high net positive charge (+7) and that the basic residues are important for membrane permeability (39). In comparison, LITX has a lower net change of +4, which may explain its inability to pass rapidly through membranes (Fig.…”
Section: Discussionmentioning
confidence: 97%
“…1) and channel mean open time (Table S1) It has not been determined whether LITX and the scorpion calcines share one or more common RyR binding sites; however, their similar modes of action suggest it is possible. Mutagenesis studies of the calcines IpTxA and maurocalcine have shown that numerous basic and acidic residues contribute to the activity of these toxins (39,44,45). A conserved Arg at position 24 in the calcines is of particular interest because it is essential for the induction of substates, but seems to have only a small involvement in full RyR openings (38,45).…”
Section: Discussionmentioning
confidence: 99%